Measurement of the time-dependent CP asymmetry in B0 -> J/ψ KS0 decays - collaboration, L; Aaij, R; Beteta, C; Adametz, A; Adeva, B; Adinolfi, M; Adrover, C; Affolder, A; Ajaltouni, Z; Albrecht, J; Alessio, F; Alexander, M; et al. (2012)
This Letter reports a measurement of the CP violation observables S_J/ψKS0 and C_J/ψKS0 in the decay channel B0 -> J/ψ KS0 performed with 1.0/fb of pp collisions at sqrt(s) = 7 TeV collected by the LHCb experiment. The fit to the data yields S_J/ψKS0 = 0.73 +- 0.07 (stat) +- 0.04 (syst) and C_J/ψKS0 = 0.03 +- 0.09 (stat) +- 0.01 (syst). Both values are consistent with the current world averages and within expectations from the Standard Model.